The quest for young asteroid families: new families, new results. Issue 4 (7th July 2018) - Carruba, V; De Oliveira, E R; Rodrigues, B; Requena, I
ABSTRACT: Asteroid families form as a result of collisions. The fragments resulting from the family-forming event are ejected into orbits near that of the parent body, and then start dynamically migrating because of gravitational and non-gravitational effects, such as the Yarkovsky force. Families that formed less than 20 Myr ago are special, since their secular angles, the longitudes of pericenter and nodes, may still converge with respect to those of the putative parent body when integrated backward in time, at the moment of family formation. This allows for obtaining age estimates and family membership with a precision not allowable for other, more evolved asteroid families. This method of family dating, the Backward Integration Method, or BIM, has been, so far, successfully applied to the case of eight asteroid families. In the last years, however, because of the astounding rate of new asteroid discoveries, several new small and compact asteroid families have been identified. In this work, we apply the BIM to 28 asteroid families not previously studied with this method. We identified four families for which we observe a possible convergence of the angles. For three of them, we obtained age estimates: at a 68.3 per cent confidence level, (3152) Jones should be 1.9^+4.3_-1.9, (7353) Kazuya should be 2.2^+1.4_-2.2, and (108138) 2001 GB11 should be 4.6^+1.6_-1.1 Myr old. (909) Ulla might be younger than ≃ 6 Myr.